Estetika Sastra Populer dalam Film Remake Aladdin (2019) Produksi Disney - Rizki Eka Putri Alda (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2020)
The movie Aladdin was chosen as an object analysis in this reasearch, purposed to elaborate formulas in the movie. Theories used in this research are Bourdieu's cultural production arena theory and Disney's